1987
DOI: 10.1002/1097-0142(19871201)60:11<2727::aid-cncr2820601125>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Thymoma. A clinicopathologic review

Abstract: The clinical and pathologic features of 283 patients with thymoma treated at the Mayo Clinic (147 female and 136 male; ages 16 years to 90 years; mean, 52 years) were examined. Forty-six percent of the patients had myasthenia gravis and 10% had other paraneoplastic phenomena. The tumors were locally invasive at operation in 32%, including 6% with metastasis to lung or pleura. Intrathoracic recurrence was noted postoperatively in 15% of those who had total excision and distant metastasis developed in 3% of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
238
3
38

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 477 publications
(291 citation statements)
references
References 43 publications
12
238
3
38
Order By: Relevance
“…In that regard it is of interest to note that a similar biphasic survival pattern has been described in sub-populations of thymoma patients with highly invasive and/or metastatic tumors (Lewis et al, 1987). Further examination of the Tim-1 mice revealed a marked gender bias for survival, as female mice died much more rapidly than their male siblings.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In that regard it is of interest to note that a similar biphasic survival pattern has been described in sub-populations of thymoma patients with highly invasive and/or metastatic tumors (Lewis et al, 1987). Further examination of the Tim-1 mice revealed a marked gender bias for survival, as female mice died much more rapidly than their male siblings.…”
Section: Discussionmentioning
confidence: 55%
“…Thymomas are comprised of neoplastic thymic epithelial cells accompanied by a variable admixture of benign lymphoblasts (Lewis et al, 1987). Although most thymomas are thought to arise spontaneously, familial forms of the disease have been reported (Matani and Dritsas, 1973;Deminatti et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous histologic classification systems, however, either adopted these characteristics independently or adopted only some of them. 2,17,[23][24][25] Conversely, taking all of these morphologic characteristics into consideration, the WHO histologic classification system divided thymomas into five groups: type A, AB, B1, B2, and B3. 21 Our previous study showed that the WHO histologic classification system reflects the invasive nature of thymoma.…”
Section: Discussionmentioning
confidence: 99%
“…Although some promote and anticipate a benign clinical course for these tumors, 6,[12][13][14][15][16] others (ourselves included) consider all thymomas as potentially malignant neoplasms. [1][2]10,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Many prior studies have documented malignant behavior in types A and AB thymomas. In our retrospective study of 71 cases of types A and AB thymomas (37 cases with follow-up information available), 18 patients (nine each of types A and AB) developed recurrence and or metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative adhesions have also been linked with the development of recurrence. 26 It has been suggested that stage I tumors be further divided into stages Ia and Ib based on the absence or presence of peritumoral adhesions. 21,29 In some studies, recurrences were observed only among patients having intraoperative adhesions.…”
Section: Discussionmentioning
confidence: 99%